Rosiglitazone‐dependent dissociation of HuR from PPAR‐γ regulates adiponectin expression at the posttranscriptional level. Issue 6 (21st March 2019) - Hwang, Jung Seok; Lee, Won Jin; Hur, Jinwoo; Lee, Hyuk Gyoon; Kim, Eunsu; Lee, Gyeong Hee; Choi, Mi-Jung; Lim, Dae-Seog; Paek, Kyung Shin; Seo, Han Geuk
ABSTRACT: Peroxisome proliferator–activated receptor (PPAR)‐γ has been implicated as a key player in the regulation of adiponectin levels via both transcriptional and posttranscriptional mechanisms. Herein, we show that PPAR‐γ interacts with human antigen R (HuR) and that the PPAR‐γ–HuR complex dissociates following activation of PPAR‐γ by rosiglitazone, a specific ligand of PPAR‐γ. This rosiglitazone‐dependent dissociation of HuR from PPAR‐γ leads to nucleocytoplasmic shuttling of HuR and its binding to the 3′‐UTR of adiponectin mRNA. PPAR‐γ with H321A and H447A double mutation (PPAR‐γ H321/447A ), a mutant lacking ligand‐binding activity, impaired HuR dissociation from the PPAR‐γ–HuR complex, resulting in reduced nucleocytoplasmic shuttling, even in the presence of rosiglitazone. Consequently, rosiglitazone up‐regulated adiponectin levels by modulating the stability of adiponectin mRNA, whereas these effects were abolished by HuR ablation or blocked in cells expressing the PPAR‐γ H321/447A mutant, indicating that the interaction of PPAR‐γ and HuR is a critical event during adiponectin expression. Taken together, the findings demonstrate a novel mechanism for regulating adiponectin expression at the posttranscriptional level and suggest that ligand‐mediated activation of PPAR‐γ to interfere with interaction of HuR could offer a therapeutic strategy for inflammation‐associated diseases that involve decreased adiponectin mRNA stability.—Hwang, J. S., Lee, W. J., Hur, J., Lee, H. G., Kim, E., Lee, G. H., Choi, M.‐J., Lim, D.‐S., Paek, K. S., Seo, H. G. Rosiglitazone‐dependent dissociation of HuR from PPAR‐γ regulates adiponectin expression at the posttranscriptional level. FASEB J. 33, 7707–7720 (2019). www.fasebj.org